2009
DOI: 10.1152/ajprenal.90746.2008
|View full text |Cite
|
Sign up to set email alerts
|

Rho kinase inhibition attenuates LPS-induced renal failure in mice in part by attenuation of NF-κB p65 signaling

Abstract: Rho kinase signaling regulates inflammatory cell migration and chemokine production. We therefore investigated the mechanisms of Rho-kinase-dependent inflammation in lipopolysaccharide (LPS)-induced renal failure. C57/BL6 mice received intraperitoneal LPS with or without daily treatment with specific Rho kinase inhibitors (Y-27632 or HA-1077; 5 mg/kg). Rho kinase inhibitors were applied in a preventive (12 or 1 h before LPS) or a therapeutic (6 h after LPS) scheme. Both protected renal function and decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 60 publications
5
42
1
1
Order By: Relevance
“…The first major finding of the current study was that YB-1 was upregulated in acute inflammatory processes in vivo, as demonstrated in the LPS-triggered model that has been widely used to characterize reversible renal inflammation processes in rodents (17,18) and additionally in a pyelonephritis model. We and others have previously demonstrated that YB-1 is involved in the onset of inflammation (4,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The first major finding of the current study was that YB-1 was upregulated in acute inflammatory processes in vivo, as demonstrated in the LPS-triggered model that has been widely used to characterize reversible renal inflammation processes in rodents (17,18) and additionally in a pyelonephritis model. We and others have previously demonstrated that YB-1 is involved in the onset of inflammation (4,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 77%
“…These mice exhibit a 50% reduction in cellular YB-1 content (13,16), and gene dosage effects in comparison with wild-type (WT) littermates have not been investigated to date. To address the role of YB-1 in the inflammatory response in vivo, we induced two renal inflammatory models in WT and YB-1 +/d mice, as follows: 1) acute peritonitis following LPS injection (17,18), and 2) unilateral ureteral obstruction (UUO), in which sterile inflammation occurs secondary to mechanical renal damage and enables the study of long-term inflammation effects.…”
mentioning
confidence: 99%
“…Moreover, Rho-kinase also plays a role in mediating lysophosphatidic acid-induced NF-B activation in endothelial cells (43) and has been implicated in neuropeptide-induced NF-B activation and subsequent stimulation of IL-8 expression in colonic epithelial cells (50). In addition, Chen et al (4) showed that the Rho exchange factor mediates NF-B activation in peripheral blood monocytes, and the importance of the renal Rho-kinase/NF-B axis has been demonstrated in vivo using lipopolysaccharideinjected mice (30). These reports indicate the existence of a mechanistic linkage between the Rho/Rho-kinase pathway and the NF-B cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NF-B activation restores systemic hypotension, ameliorates septic myocardial dysfunction and vascular derangement, inhibits multiple proinflammatory gene expression, diminishes intravascular coagulation, reduces tissue neutrophil influx, and prevents microvascular endothelial leakage (31). Studies using a CLP model have shown that inhibition of NF-B activation significantly improves survival (22,30,33).…”
Section: Discussionmentioning
confidence: 99%